The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1097/00004694-199905000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Eight pediatric patients who underwent nine simultaneous ipsilateral femoral and tibial lengthenings with the Ilizarov external fixator were reviewed. The patient's demographics, diagnoses, corticotomy levels, mechanical axes, healing indices, amounts of lengthening, and complications were recorded. The patients' average age was 8 years 10 months (5 years 4 months-15 years 10 months) with an average follow-up of 49 months (30-88 months). The percentage of femoral lengthening averaged 16.7% (8-23%) with an aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The new bone formed at the distraction site generally requires a much longer consolidation period than distraction period, resulting in a bone healing index (time in external fixation/length gained) of more than 30 days per centimeter of adult limb lengthening. 6 7 8) A long duration of external fixation for distracting and stabilizing the osteotomy site increases the complications and causes inconvenience to the patients. 9) …”
mentioning
confidence: 99%
“…The new bone formed at the distraction site generally requires a much longer consolidation period than distraction period, resulting in a bone healing index (time in external fixation/length gained) of more than 30 days per centimeter of adult limb lengthening. 6 7 8) A long duration of external fixation for distracting and stabilizing the osteotomy site increases the complications and causes inconvenience to the patients. 9) …”
mentioning
confidence: 99%
“…Curran et al [ 15 ] reported eight paediatric patients who underwent nine simultaneous ipsilateral femoral and tibial lengthenings with the Ilizarov external fixator. Four complications in three patients occurred as a result of the lengthening process.…”
Section: Discussionmentioning
confidence: 99%